Benefits of adopting improved forages in smallholder farms in Central America: An ex post analysis - Holmann, Federico J.; Argel M., Pedro J.; Pérez, E. (2009)
The objective of this study was to estimate the benefits received by producers who adopted improved forages as part of a project[1] carried out in Guatemala, Honduras, Nicaragua, and Costa Rica in terms of increased productivity, stocking rate, and income due to the additional sale of milk and beef in retribution for family labor. Data were obtained from a survey carried out in 2007 that included nine producers in Guatemala, 16 in Honduras, 16 in Nicaragua, and 15 in Costa Rica who had adopted different grass and legume options during the period 2003-2007. The area planted to improved pastures increased in all countries, ranging from 12% in Guatemala to 105% in Nicaragua. Except for Guatemala (where the animal inventory decreased almost 11% due to Hurricane Stan), all countries expanded their herds (between 34% and 41%) in practically all animal categories, not only adult cows. On-farm milk production during the dry season increased 9% in Guatemala, 47% in Honduras and Nicaragua, and 71% in Costa Rica. Milk production during the rainy season remained practically invariable in Guatemala, but increased 48% in Honduras, 19% in Nicaragua, and 53% in Costa Rica. On the other hand, these increases in milk production were also favored by the rise in milk prices in all countries, ranging from 7% in Nicaragua to 36% in Costa Rica during the dry season and from 4% in Nicaragua to 36% in Costa Rica during the rainy season. Beef production accordingly increased 15% in Nicaragua, 46% in Honduras, and 74% in Costa Rica. similar to the trend observed in milk production, beef production did not increase in Guatemala because producers had to sell animals to recover from the losses caused by Hurricane Stan. Likewise, at the end of the project, producers in all countries received higher prices as compared with those obtained at the beginning of the project. The price of beef paid to the producer increased 9% in Guatemala, 4% in Honduras, 5% in Nicaragua, and 11% in Costa Rica. Because of these significant increases in annual milk and meat production, major increases were also observed in the annual net income of farms, reaching 32% in Guatemala, 288% in Honduras, 177% in Nicaragua, and 238% in Costa Rica. These extraordinary increases in net income can be attributed to three factors: (1) the higher milk price in 2007 as compared with that of 2003; (2) higher production due to the better diet; and (3) increased production due to the higher stocking rate allowed because of the adoption of and increase in area sown to improved forages. The increase in the net income of these producers has triggered an increase in the economic returns to family labor, as compared with the commercial value of a day’s wages. Therefore, the returns to family labor in Guatemala went from 3.1 times the value of the minimum wage in 2003 to 6.0 times that value in 2007, representing a 97% increase. In Honduras, the returns to family labor went from 2.9 times the minimum wage in 2003 to 9.8 times that value in 2007, representing a 238% increase. Similarly, in Nicaragua these returns represented a 104% increase and in Costa Rica a 200% increase.